n = 0 ∑ ∞ ( 4 n + 1 ) ( 4 n + 3 ) ( n + 1 ) 1
If the series above can be expressed in the form
B π A − ln C ,
where A , B and C are positive integers, find A + B + C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you please explain how you got the second step?
Log in to reply
Do you mean this one: = n = 0 ∑ ∞ 3 2 [ 4 n + 1 1 − 4 n + 3 3 + 4 n + 4 2 ] ? Just partial fractions .
Log in to reply
Nope , the next one.
Log in to reply
@Nihar Mahajan – If you write the first few terms of 4 n + 1 1 − 4 n + 3 3 + 4 n + 4 2 , we get
1 − 3 3 + 4 2 , 5 1 − 7 3 + 8 2 , 9 1 − 1 1 3 + 1 2 2 , …
Without simplifying all these terms, each of these terms have 3 fractions.
Let's compare the first fractions in each term:
1 , 5 1 , 9 1 , 1 3 1 , …
All of these fractions can be expressed as ∫ 0 1 1 d x , ∫ 0 1 x 4 d x , ∫ 0 1 x 9 d x , …
Taking the sum of all these "first fractions" alone gives us
∫ 0 1 ( 1 + x 4 + x 8 + ⋯ ) d x
The integrand is an infinite geometric progression sum , with first term 1 and common ratio x 4 , this allows us to simplify the integral to ∫ 0 1 1 − x 4 1 d x .
Similarly, by comparing the second fractions in each terms and taking their sum gives us an integrand of another infinite geometric progression sum with first term 3 x 2 and common ratio x 4 , thus the sum is ∫ 0 1 1 − x 4 3 x 2 d x .
And of course, we can work out the third fractions as well to obtain the sum of ∫ 0 1 1 − x 4 2 x 3 d x .
Combining these three integrals gives us the following line.
You rarely post solutions in calculus. But when u post it is really elegant. Elegance over 9000!
Here's an overkill approach:
Let f ( x ) = n = 0 ∑ ∞ ( 4 n + 1 ) ( 4 n + 3 ) ( 4 n + 4 ) 4 x 4 n + 4 , so we want to find f ( 1 ) . Differentiating it a couple of times yields
f ( 4 ) ( x ) = = = = n = 0 ∑ ∞ ( 4 n + 1 ) ( 4 n + 3 ) ( 4 n + 4 ) 4 ( 4 n + 1 ) ( 4 n + 2 ) ( 4 n + 3 ) ( 4 n + 4 ) x 4 n n = 0 ∑ ∞ ( 1 6 n + 8 ) x 4 n 1 6 n = 0 ∑ ∞ n x 4 n + 8 n = 0 ∑ ∞ x 4 n , an infinite AGP sum and an infinite GP sum ( 1 − x 4 ) 2 1 6 x 4 + 1 − x 4 8 = ( 1 − x 4 ) 2 8 + 8 x 4
Integrating back gives us
f ( 1 ) = = = = = ∫ 0 1 ∫ 0 z ∫ 0 y ∫ 0 w ( 1 − v 4 ) 2 8 + 8 v 4 d v d w d y d z ∫ 0 1 ∫ 0 z ∫ 0 y ( − w 4 − 1 4 w − ln ∣ 1 − w ∣ + ln ∣ w + 1 ∣ + 2 tan − 1 w ) d w d y d z ∫ 0 1 ∫ 0 z ( − ln ( 1 − y 2 ) − ( y − 1 ) ln ∣ 1 − y ∣ + y ln ∣ 1 + y ∣ + y ln ∣ y + 1 ∣ + ln ∣ y + 1 ∣ + 2 y tan − 1 y ) d y d z ∫ 0 1 2 1 ( z 2 ln ∣ z + 1 ∣ − 2 z ln ∣ 1 − z 2 ∣ + ( − z 2 + 2 z + 1 ) ln ∣ 1 − z ∣ + 2 ( z 2 + 1 ) tan − 1 ( z ) + 2 x ln ∣ z + 1 ∣ − ln ∣ z + 1 ∣ ) d z 3 π − ln 2
Note that I've skipped out a lot of integration steps which are all extremely tedious to evaluate. You should only be doing this method if you really have nothing else better to do or have no life .
Problem Loading...
Note Loading...
Set Loading...
Synopsis : We convert the series it into a simple integral of a sum of a convergent infinite geometric progression, we then evaluate this integral by partial fractions decomposition .
n = 0 ∑ ∞ ( 4 n + 1 ) ( 4 n + 3 ) ( n + 1 ) 1 = 3 2 n = 0 ∑ ∞ [ 4 n + 1 1 − 4 n + 3 3 + 4 n + 4 2 ] , = 3 2 n = 0 ∑ ∞ ∫ 0 1 ( x 4 n − 3 x 4 n + 2 + 2 x 4 n + 3 ) d x = 3 2 ∫ 0 1 1 − x 4 1 − 3 x 2 + 2 x 3 d x , = 3 2 ∫ 0 1 ( 1 − x ) ( 1 + x ) ( x 2 + 1 ) ( 1 − x ) 2 ( 2 x + 1 ) d x = − 3 2 ∫ 0 1 ( 1 + x ) ( x 2 + 1 ) ( x − 1 ) ( 2 x + 1 ) d x = − 3 2 ∫ 0 1 ( x 2 + 1 x − 2 + x + 1 1 ) d x = − 3 2 ∫ 0 1 ( x 2 + 1 x − x 2 + 1 2 + x + 1 1 ) d x = − 3 2 [ 2 1 ln ∣ x 2 + 1 ∣ − 2 tan − 1 ( x ) + ln ∣ x + 1 ∣ ] 0 1 = − 3 2 ( 2 3 ln 2 − 2 π ) = 3 π − ln 2 Partial fractions - cover up rule Geometric series Apply partial fractions
This means A = 1 , B = 3 , C = 2 ⇒ A + B + C = 6 .